A Multi-Wavelength Raman Study of Some Oligothiophenes and Polythiophene - Stewart F. Parker; Jessica E. Trevelyan; Timothy Smith; Kenneth P. J. Williams (Physchem, 2023)
We have measured the Raman spectra of some oligothiophenes (bithiophene, terthiophene, quarterthiophene, sexithiophene and octithiophene) and polythiophene with wavelengths from 325–1064 nm (3.815–1.165 eV). All of the materials give good quality spectra with 1064 nm excitation, although there is weak background fluorescence for some of them. The UV lines of 405 and 324 nm generally provide good-quality spectra, albeit with significant fluorescence for bithiophene and quarterthiophene. Surprisingly, there is little difference between the relative intensities (i.e., the ratio of a band’s intensity as compared to the strongest band) of the spectra with the different excitation wavelengths. However, close inspection of the 2000–3200 cm−1 region of octithiophene and polythiophene with 325 and 405 nm excitation shows several modes in this region that can be assigned to combinations and overtones involving the ~1440 cm−1 C–C ring stretch that do not appear with 1064 nm excitation. The presence of overtones and combinations with anomalously large intensities is a hallmark of resonance Raman spectroscopy.